Cyber Security Politics : Socio-Technological Transformations and Political Fragmentation. - Dunn Cavelty, Myriam. (CSS Studies in Security and International Relations Series, 2022)
This book examines new and challenging political aspects of cyber security and presents it as an issue defined by socio-technological uncertainty and political fragmentation.